Potential of Livestock Production Systems: Explaining Employability and Milk Productivity Through Multivariate Typology - S PATHADE, SANTOSH; SINGH, B P; CHANDER, MAHESH; BARDHAN, D; RAM VERMA, MED; SINGH, Y P (The Indian Journal of Animal Sciences, 2022)
A study was conducted in four different agro-climatic zones of Maharashtra state in India. The typology was developed with an aim to identify livestock production system, employment generation, and milk productivity of livestock production system. Multivariate statistical technique, i.e. Cluster analysis (CA) was used to classify groups of farm households with similar farm characteristics into four homogenous clusters, viz. households possessing small landholding, a larger high yielding dairy stock with small goat flock size (37.5%); small landholding with a small stock of high yielding dairy animal and small goat flock size (39%); large landholding with large high yielding dairy stock and small flock size (13.5%); small landholding with small high yielding dairy stock and large flock size (10%). It was observed that 47.5% of the respondents had dairy and 31.3% had a goat production system. The total man-days generated for family labour were high (165.87) for cluster 2 households while, for hired labour, man-days generated were high for cluster 4 households. Milk yield index was significantly high for cluster 3 and cluster 1 households. Spearman correlation revealed that independent variables, viz. total SAU, flock size, income from dairy and goat production system positively correlated with milk productivity, employment generation (man-days) and gross annual income. Multiple regression analysis revealed that the integration of dairy and goat farming along with technology adoption significantly influenced the employment generation of small landholders.